Avian responses to forest fragmentation during the breeding and non-breeding seasons - Verga, Ernesto Gustavo (2020)
Forest fragmentation represents a threat to several bird species worldwide. Several factors can change across seasons (e.g. bird perception of the landscape, weather conditions, biotic interactions), which can modify the response of bird populations to forest fragmentation. However, most studies have been conducted only during the breeding season. Here we assessed the relationship between forest fragmentation (patch area and patch isolation) with population abundances of resident species during both the breeding and the non-breeding seasons. Bird population abundances (all species in the community, subsets of forest and habitat generalist species and for individual species) were estimated across a gradient of area-isolation in a semi-arid forest in Cordoba, Argentina. Population abundance of the overall avian community and of the subset of forest species declined with patch area reduction independently of the season. By contrast, the subset of habitat generalist species was not affected by patch area reduction or by the increase in patch isolation, either during the breeding or during the non-breeding season. When the analyses were carried out for individual species, we found four forest species and one habitat generalist species whose responses (the relationship between population abundance and patch area or with isolation) were different between breeding and non-breeding seasons. The negative effects of forest fragmentation were found mainly during the breeding season. Our results suggest that reduction of patch area may lead to a reduction of more than 65% of the population abundance of forest bird species, during both the breeding and the non-breeding season. Therefore, there is an urgent need to conserve large forest patches within the region as irreplaceable elements for the conservation of populations of several species.